Efeitos da terapia por fotobiomodulação laser no processo de integração de enxerto de pele total, em ratos - Oliveira, Maria Carolina Derencio (2023)
The skin grafting technique is defined by the transfer of a skin segment to a damaged body area, without a vascular pedicle. The graft integration process is complex, since it is necessary to reestablish the blood supply and consequently many complications are triggered. To avoid recurrence, low-cost, easy-to-apply treatments are sought and with local actions that stimulate the healing process. Recently, laser photobiomodulation (PBM) began to be investigated in this area, due to it is trophic-regenerative effects described in the literature for various skin wounds. However, the studies are still initials, with inconclusive protocols and dosimetry. In view of this, the objective of this thesis was to evaluate the relationship between power and irradiation time of laser PBM in fibroblasts, at red (660 nm) and infrared (808 nm) wavelengths, further investigating it as a therapeutic proposal to optimize the full-thickness skin grafts integration, when applied in the recipient area or as a post-surgical treatment. In the first study and in vitro, human skin fibroblast cells were irradiated with 1 J energy, 50 mW power and 20 s time or 100 mW power and 10 s time, for each wavelength. After evaluating cell proliferation and the inflammatory mediator interleukin-6 (IL-6), it was concluded that the association of higher potency with shorter irradiation time was more effective in stimulating fibroblasts and reducing IL-6. In the in vivo studies, 60 rats were used and all of them underwent full-thickness skin graft surgery, measuring 5x3 cm. In the first study, the animals received only one PBM application in the recipient area, with the aim of biostimulating the bed to receive the graft. In the second study, the animals received PBM immediately after surgery, 24 hours and 48 hours later, totalizing three applications. In both studies, analyzes were performed on the 3rd and 7th day after the procedure, with photographic captures and biological samples being collected. The results of the first indicated a lower necrosis percentage and better morphological characteristics with the 660 nm laser. The results of the second showed better performance of the 808 nm laser, with lower necrosis percentages and better morphological conditions.